Magnetite/graphene oxide/Prussian blue composite with robust effectiveness for electromagnetic interference shielding. Issue 2 (15th January 2022) - Ata, Sadia; Bukhari, Syed A.; Bibi, Ismat; Mohsin, Ijaz-ul; Shoaib, Muhammad; Majid, Farzana; Iqbal, Munawar; Alshammari, Fwzah H.; Alfryyan, Nada; Alwadai, Norah
Abstract: Considering the promising efficiency of composites, in the current study, a graphene oxide (GO)-magnetite-Prussian blue (PB) composite material was prepared. The composite exhibited electrical conductivity, magnetic permeability, and permittivity nature, and was evaluated using electromagnetic interference (EMI) shielding studies. GO was developed by the Hummer's method, ferrite (Fe3 O4 ) was incorporated by the sol-gel method, and PB was introduced in the mixture by an in-situ process. The fabricated samples were studied by X-ray diffraction, Raman Spectroscopy, Fourier-transform infrared spectroscopy along with EMI shielding efficiency (SE) evaluation. The SE of −71.66 dB of reflection losses was measured at a frequency of 1.5 MHz. The GO/Fe3 O4 /PB composite provided the best results for the detection in the 1–18 MHz frequency range because of its excellent electric and magnetic properties. The obtained results demonstrated that the GO/Fe3 O4 /PB composite has promising potential applications in EMI shielding.